Extreme magnetic field-boosted superconductivity - Ran, Sheng (Nat Phys, 2019)
Applied magnetic fields underlie exotic quantum states, such as the fractional quantum Hall effect(1) and Bose–Einstein condensation of spin excitations(2). Superconductivity, however, is inherently antagonistic towards magnetic fields. Only in rare cases(3–5) can these effects be mitigated over limited fields, leading to re-entrant superconductivity. Here, we report the coexistence of multiple high-field re-entrant superconducting phases in the spin-triplet superconductor UTe(2) (ref. (6)). We observe superconductivity in the highest magnetic field range identified for any re-entrant superconductor, beyond 65 T. Although the stability of superconductivity in these high magnetic fields challenges current theoretical models, these extreme properties seem to reflect a new kind of exotic superconductivity rooted in magnetic fluctuations(7) and boosted by a quantum dimensional crossover(8).